Politiques environnementales brésiliennes : intentions et réalités - Neli Aparecida de Mello-Théry (EchoGéo)
This article is a reflection on the environmental policies elaborated and implemented over the last fifteen years, in particular those on biodiversity conservation, climate change and the Law on Forests (former Forestry Code). The contradictions, advances and setbacks in the environmental policy of the Lula and Dilma governments are visible on the national scene and environmental risks continue to increase. Some specific plans and programs (particularly on deforestation in Amazonia) and climate change policy have made progress. Others have worsened a rather precarious situation, as was the case with the Forest Act. Our analysis will show the evolutions and continuities of current public policies.